Pengaruh Faktor-Faktor Kekuasaan Kepala Sekolah Terhadap Kinerja Guru pada SMA Negeri di Kabupaten Minahasa Utara - Rumapea, Patar (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts: The problem and objectives of this research are how the condition of power that used by the principal on the Public Senior High Schools in the Regent of North Minahasa, and to explain the influence of the factors of power by the principal to the teacher’s performance. This research was conducted in North Minahasa on six Public Senior High Schools with 69 respondents sample. It used stratified random sampling technique. Data was collected by using questionnaire technique in the form of statement/questions measured by Likert scale. The analysis method used here is descriptive analysis and multiple linear regression analysis. The results of this research indicated that: (1) the exertion of power by the principal to increase the teacher’s performance is more of legitimate power. (2) besed on determinant coefycient value, that symoltantly usage of legitimate power, reward power, coercive power, expert power, and referent power have influence to teacher’s performance. Therefore, it is suggested that the further research could try to obtain other variables which are possibly better in establishing an increasing model of the teacher’s performance. Keywords: factors of power, and performance